The measurement of household consumption expenditures - Martin Browning; Thomas Crossley; Joachim Winter (Institute for Fiscal Studies (IFS), 2014)
Household-level data on consumer expenditures underpins a wide range of empirical research in modern economics, spanning micro- and macroeconomics. This research includes work on consumption and saving, on poverty and inequality, and on risk sharing and insurance. We review different ways in which such data can be collected or captured: traditional detailed budget surveys, less onerous survey procedures that might be included in more general surveys, and administrative or process data. We discuss the advantages and difficulties of each approach and suggest directions for future investigation.
Keywords: 330; expenditure; survey data; administrative data; measurement error